The Efficacy and Mid-term Durability of Urethral Sphincter Injections of Platelet-Rich Plasma in Treatment of Female Stress Urinary Incontinence - Chiang, Ching-Hsiang; Kuo, Hann-Chorng (Frontiers in Pharmacology, 2022)
Aims: This study investigated the therapeutic effect of repeated urethral sphincter injections of autologous platelet-rich plasma (PRP) in treatment of stress urinary incontinence (SUI) in women due to intrinsic sphincter deficiency (ISD) refractory to medical treatment or after the first anti-incontinence surgery. Methods: Twenty-six women with SUI due to urodynamically proven ISD were prospectively enrolled. Five milliliters of PRP (2.5–5 times of the platelet concentrations in peripheral blood) were injected into the external sphincter at 5 sites, with 4 treatments at monthly interval. The primary end-point was post-treatment Global Response Assessment (GRA, scored 0-3) score after four PRP treatments. A GRA ≥ 2 was considered as a successful result. The secondary endpoints included changes in visual analog scale (VAS) of SUI and urodynamic parameters. The follow-up date was 12 months after the 4th PRP treatment. Results: The mean age was 61.7 ± 15.3 years. The overall success rate was 50% with the post-treatment mean GRA of 1.5 ± 1.1. Complete dryness was achieved in 12 patients (46.2%) after the PRP treatment, and 7 (26.9%) kept total continence at 12 months. The mean VAS of SUI score decreased significantly from 6.4 ± 2.3 to 3.9 ± 2.3 after treatment (p < 0.001). The abdominal leak point pressure increased significantly from 117.5 ± 63.8 to 133.6 ± 61.7 cmH2O (p = 0.045). No perioperative adverse events or severe complications occurred, except 1 (3.8%) patient reported straining to void which was self-limited. Conclusions: Repeated urethral sphincter injections of autologous PRP are a safe procedure that provides significant reduction in the severity of female SUI and a mid-term durability, suggesting PRP treatment is effective to increase urethral sphincter resistance for female SUI.